Water Quality Monitoring with Fuzzy Logic Control based on Graphical Programming - Mochammad Hannats Hanafi Ichsan; Wijaya Kurniawan; Miftahul Huda (Universitas Ahmad Dahlan, 2016)
Water quality is the most important aspect to ensure success in various aspects of life, for example in the shrimp ponds. On a shrimp pond, water conditions are very vital because it has a very strict threshold. Unstable water conditions will affect growth and condition of shrimps, eat passion of shrimps, until their ability to survive greatly affect the survival of the shrimps. The percentage of farmers harvesting shrimps if the water did not have good conditions then the farmers will suffer significant losses if yields were not as expected, began from the amount of shrimp that was reduced due to death or the quality of the shrimp were judged from the size of the shrimp. So the authors wanted to do research on how to maintain the quality of the water in shrimp pond so that the water quality is maintained. To overcome this, we need to monitor water conditions based on the level of salinity and turbidity of water in order to stay in good condition. In this case, the researchers used fuzzy logic to monitor the amount of water quality and water volume. In this study only conducted water quality monitoring process but to do water changes to a certain condition still conducted manually. As well as the programming language used as the NI LabVIEW graphical programming with the application form to see monitoring of water quality so that water conditions are well preserved.